Effect of Pro-Inflammatory Cytokines on Lacrimal Gland Myoepithelial Cell Functions. - Kim, Michelle (Gina). (Tufts Archival Research Center, 2018)
Sjögren’s syndrome is a systemic inflammatory disease that affects the lacrimal gland and is the leading cause of aqueous-deficient dry eye. The lacrimal gland is the main contributor of the aqueous layer of the tear film. Overall, there are three different cell types in the lacrimal gland: acinar, ductal, and myoepithelial cells. Myoepithelial cells are responsible for the production of extracellular matrix and basement membrane components and play a role in tear secretion. These cells also contract to help expel secretory products from the acinar cells; this contraction is regulated by oxytocin. In chronic inflammatory diseases of the lacrimal gland, such as Sjögren’s syndrome, there is reduced production of tears leading to dry eye disease, which may be due to impaired function of myoepithelial cells. In this study, isolated myoepithelial cells from SMA-GFP mice were grown in culture and treated with or without interleukin-1 (IL-1), which is a pro-inflammatory cytokine, in order to study the effect of IL-1 on myoepithelial cells. Western blotting and immunofluorescent staining experiments were conducted in order to ascertain the presence and expression of the oxytocin receptor and the key contractile proteins of interest (SMA and calponin).Our study confirmed that myoepithelial cells can successfully be isolated and cultured from SMA-GFP mice, which would allow future experiments to be conducted with more ease as compared to studies in whole animals. Through these experiments, we also confirmed that these cells expressed oxytocin receptor, and that treatment with IL-1 leads to a significant decrease in expression of key contractile proteins of interest (SMA and calponin). Based on our findings, we can conclude that our data support the hypothesis that chronic inflammation of the lacrimal gland and increased levels of IL-1 leads to degradation of SMA and calponin, which overall impairs the contraction of myoepithelial cells and limits tear secretion.